2009
DOI: 10.1057/pcs.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Thinking through others: Cultural psychology and the psychoanalytic treatment of immigrants

Abstract: Today's immigrants often have the twenty-first-century desire to maintain the cultural ideals and practices that their predecessors were eager to shed. This paper is concerned with psychoanalytic receptivity to these ideals and practices and, more abstractly, with the conception of cultural difference that informs psychoanalytic theory and practice. The author introduces a conceptual framework from cultural psychology to theorize differences in everyday practice, thought, feeling and relationship patterning ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It entails listening to what lies beneath these meanings, how and in which context they were formed, the intrapsychic and extrapsychic implications these meanings have for the clients' day-to-day life, the anxiety that is produced in the client's articulation of indigenous narrative for both the client and the therapist. Harlem (2009) has suggested that this type of listening involves interpreting the client's desires, fears, behaviors, and relationships in the context of a cultural meaning system by "thinking by means of the other" (p. 281). Listening to indigenous narrative necessitates a collaborative relationship in which there is a recognition that the therapist's cultural narrative and the client's cultural narrative, and that accompanying motivations interplay unconsciously.…”
Section: Recognize Indigenous Narrativementioning
confidence: 99%
“…It entails listening to what lies beneath these meanings, how and in which context they were formed, the intrapsychic and extrapsychic implications these meanings have for the clients' day-to-day life, the anxiety that is produced in the client's articulation of indigenous narrative for both the client and the therapist. Harlem (2009) has suggested that this type of listening involves interpreting the client's desires, fears, behaviors, and relationships in the context of a cultural meaning system by "thinking by means of the other" (p. 281). Listening to indigenous narrative necessitates a collaborative relationship in which there is a recognition that the therapist's cultural narrative and the client's cultural narrative, and that accompanying motivations interplay unconsciously.…”
Section: Recognize Indigenous Narrativementioning
confidence: 99%
“…In supervision, the supervisor would apply that same stance to both the client and supervisee, viewing them as being best positioned to provide education about their own individual multiculturalism. When examining contemporary psychoanalytic thought visa `-vis culture, cultural humility would seem most consistent with Harlem's (2009) perspective on "thinking through others" and Leary's (2012) discussions about engaging the adaptive challenge, where we "open ourselves to the different stories differently situated others have to tell in their own voices and on their own terms" (Leary, 2014, p. 253).…”
Section: Components Of a Culturally Humble Psychoanalytic Supervision...mentioning
confidence: 98%
“…Reducing a client's individual struggle to terms with which the clinician is familiar, rather than using the relational skills of co-construction of meaning and acknowledgement of not knowing, represents the clinical social worker's challenge in working with a culturally different population: misunderstanding can arise from trying to understand on the clinician's experiential terms that are unconsciously assigned universal validity. Harlem ( 2009 ) suggests, instead, that emotional life is culturally constructed. Rosaldo ( 1984 ), as cited in Harlem ( 2009 ), writes that "feelings are not substances to be discovered in our blood but social practices organized by stories that…are structured by our forms of understanding" (p. 143).…”
Section: A Critical Clinical Momentmentioning
confidence: 99%
“…Harlem ( 2009 ) suggests, instead, that emotional life is culturally constructed. Rosaldo ( 1984 ), as cited in Harlem ( 2009 ), writes that "feelings are not substances to be discovered in our blood but social practices organized by stories that…are structured by our forms of understanding" (p. 143). Therefore, although Jessica was not incorrect in understanding Naresh's core issues as expressing separation and attachment confl icts, she was out of alignment with the culturally specifi c dimensions of how separation and attachment can be negotiated in a different cultural context.…”
Section: A Critical Clinical Momentmentioning
confidence: 99%